Analytical and finite element solution of the sliding frictional contact problem for a homogeneous orthotropic coating‐isotropic substrate system. Issue 3 (31st January 2019) - Yilmaz, K. B.; Çömez, İ.; Güler, M. A.; Yildirim, B.
Abstract: In this study, the contact problem for a homogeneous orthotropic coating‐isotropic substrate system is considered. The rigid stamp slides over the orthotropic coating whose bottom surface is bonded to a homogeneous isotropic substrate. The bottom surface of the substrate is fixed to the ground. By using Fourier integral transforms, the partial differential equations are converted to ordinary differential equations (ODEs). The displacement components for coating and substrate are obtained by solving the corresponding ODEs. A numerical study based on finite element analysis (FEA) is also conducted. The results from the analytical formulation are directly compared with the FEA results. The effects of orthotropic and isotropic material properties, coefficient of friction between the sliding surfaces, geometrical properties on the contact stresses and contact widths are presented. The results of this study may help tribology engineers to understand the deformation characteristics of the coating‐substrate systems and enhance their knowledge on friction and wear mechanisms of sliding surfaces. Abstract : In this study, the contact problem for a homogeneous orthotropic coating‐isotropic substrate system is considered. The rigid stamp slides over the orthotropic coating whose bottom surface is bonded to a homogeneous isotropic substrate. The bottom surface of the substrate is fixed to the ground. By using Fourier integral transforms, the partial differential equations are converted to ordinary differential equations (ODEs). The displacement components for coating and substrate are obtained by solving the corresponding ODEs. A numerical study based on finite element analysis (FEA) is also conducted. The results from the analytical formulation are directly compared with the FEA results. The effects of orthotropic and isotropic material properties, coefficient of friction between the sliding surfaces, geometrical properties on the contact stresses and contact widths are presented. The results of this study may help tribology engineers to understand the deformation characteristics of the coating‐substrate systems and enhance their knowledge on friction and wear mechanisms of sliding surfaces.